Faktor-Faktor Yang Berhubungan Dengan Perilaku Personal Hygiene Saat Menstruasi Pada Siswi Smp Pgri Depok II Tengah Jawa Barat Tahun 2020 - Nabila Azzahra; Retno Mardhiati Adiwiryono (Poltekkes Kemenkes Malang, 2020)
Having a good personal hygiene behavior especially during menstruation can reduce the risk of reproductive health problems. The aim of this study is to find out factors associated with personal hygiene during menstruation in student of SMP PGRI Depok II Tengah West Java 2020. This study uses quantitative method with a cross sectional design study. This study is conducted in December 2019 to May 2020. The population of this study is the entire student in class VII and VIII. The number of sample in this study is 94 which conducted with quota sampling. This study uses a primer data which uses google form questionnaire as an instrument to collect a data. The data is analyzed using univariate and bivariate analysis with chi square. Univariate analysis results show that 76,6 percent respondents do not have good personal hygiene behavior during menstruation, 72,3 percent have the ideal age of menarche, 58,5 percent have low knowledge, 70,2 percent have negative attitudes, 84 percent have incomplete hygiene facilities and infrastructure in school, 91,5 percent are exposed to information, and 63,8 percent have sufficient peer support. Bivariate analysis show that there is a significant association between the completeness of hygiene facilities and infrastructure in school with personal hygiene behavior during menstruation with Pvalue equal 0,008.